(untitled) (Journal of Plant Disease Sciences, 2025)
This study investigates the potential of five strains (designated Bb1 to Bb5) as biocontrol agents against , the pathogen responsible for turcicum leaf blight and plant growth promotion of maize. Among the tested strains, Bb1 demonstrated the most significant antagonistic activity, achieving an impressive 81.67% inhibition of growth . The study also assessed the plant growth promoting traits of Bb1, revealing that it exhibited 69.93% iron chelation efficiency, 60.67% phosphate solubilization efficiency and indole-3-acetic acid (IAA) production of 18.98 μg/ml. Overall, Bb1 stands out as a dual-function agent that is effective against while also enhancing plant growth.